(untitled) (Superficies y Vacío, 2012)
Silver nanoparticles were synthesized using a green chemistry method. Stable silver nanoparticles in a colloidal aqueous solution were prepared successfully by the chemical reaction of silver nitrate (AgNO3) and Opuntia ficus indica aqueous extract, used as both, reducing and stabilizing agent. Nanoparticle size, morphology and optical properties were analyzed by using transmission electron microscopy (TEM) and UV-Vis spectroscopy, respectively. TEM images revealed a nanoparticle average size of 23 nm. An absorption band centered around 398 nm was observed, this absorption corresponds to the surface plasmon resonance (SPR) of the silver nanoparticles.